Post mastectomy breast reconstruction with autologous latissimus dorsi flap: a study of 30 cases - Singla, Shipra; Kakkar, Vikas; Singh, Rana Ranjit (International Surgery Journal, 2020)
Background: There is a growing demand for breast reconstruction and among the plethora of breast reconstruction techniques, the latissimus dorsi (LD) flap is a versatile, reliable means for soft tissue coverage, providing form and function with acceptable perioperative and long-term morbidities for a variety of breast defects. The aim of this study was to find out the advantages of immediate breast reconstruction in terms of postoperative morbidity and patient satisfaction with respect to her expectations. Methods: The study was conducted in the Department of General Surgery at Sri Guru Ram Das Institute of Medical Sciences and Research, Vallah, Sri Amritsar. Thirty female patients who had undergone immediate breast reconstruction with latissimus dorsi flap after modified radical mastectomy attending surgery department from November 2017 to September 2019 were taken. The follow up was done to find out post-operative complications and a statistical scoring was done according to rating scale of quality of life. Results: Most common complication after breast reconstruction with LD flap was found to be seroma formation (50%) followed by wound infection and flap necrosis 25% each while flap necrosis >20% was not found in any case. For emotional feeling regarding health, social activities, overall health and quality of life; there was significant improvement after surgery. Conclusions: It can be concluded that immediate breast reconstruction with autologous latissimus dorsi flap is the treatment of choice following mastectomy in cases of breast carcinoma, whenever possible.